O governo eletrônico em Moçambique: uma reflexão sobre políticas públicas de informação - Nharreluga, Rafael Simone (2006)
It examines the political, social and professional dimension of the government information, in the representation of the e-government project in Mozambique, as base for governance and social use of information. The fundamental principle for this research sets a relation between state and information. It adopts the state definition as relation and as informational field. Presents a picture of definitions on information and information policy, providing the necessary background against which information policy development can be undertaken. The theoretical dimension from the state and the approach of the information public policies are intercrossed. And in such a way, the result suggests outlines to the e-government notion as much in its argument of mediation of relations between state and civil society as in its historical context related to the discourse of information society. It briefly discusses the notion of information society from which they are distinguished two types of views, and the implications of these are interrelated with the information area and the process of information policy construction. Under this theoretical representation, the government programs which shaped the process of Mozambique state and society construction and reform after 1975 are analyzed, aiming the view to the 2000-2005 period programs which are referee for the e-government project in Mozambique. The analysis of these programs was based on mediation of information aspects which generally result of institutional rules and mechanisms to support and being supported for the relations between state and civil society. And it sought to understand the configuration of the government information, as well as the existence or not of information public policies formulation and implementation moments in such programs. The results point a fragility of the social and professional dimension of the government information and the absence of an information project for the state and the e-government construction in Mozambique.